What can Social Psychologists Learn from Architecture? The Asylum as Example1. (27th August 2013) - Foster, Juliet L.H.
Abstract In this paper I argue for a stronger consideration of the possible relationship between social psychology and architecture and architectural history. After a brief review of some of the ways in which other social psychologists have sought to develop links between social psychology and history, I consider the utility of architecture in more depth, especially to the social psychologist interested in the development of knowledge and understanding. I argue that, especially when knowledge is institutionalised, the design and use of buildings might have a particular contribution to make to the way we can understand how phenomena have been understood and approached in the past. Although many examples are relevant, I consider the case of the psychiatric hospital (or "asylum") in more detail.